Time series estimation of Malaysia's export and import demand : a dynamic old method - Abu Bakar, Nor'Aznin (Universiti Utara Malaysia, 2000)
This paper examines the long-run relationship of export and import demand of Malaysia using time series analysis techniques that address the problem of non-stationarity. Specifically, the dynamic OLS method and the Johansen Maximum Likelihood are employed to estimate the price and income elasticities. The price and income elasticities for export demand are -0.35 and 0.20 respectively. While the price and income elasticities for import demand are -1.24 and 0.90 respectively. Obviously, the Marshall-Lerner conditions are easily met as the sum of the price elasticities of export and import demand is greater than one, suggesting that appreciations (depreciations) in exchange rates can worsen (improve) the current account in a period of one year.